A Structured Approach to Capture the Lived Experience of Spinal Cord Injury: Data Model and Questionnaire of the International Spinal Cord Injury Community Survey. (February 2017) - Fekete, Christine; Post, Marcel W.M.; Bickenbach, Jerome; Middleton, James; Prodinger, Birgit; Selb, Melissa; Stucki, Gerold
Abstract : Abstract: The International Spinal Cord Injury (InSCI) community survey has been developed to collect internationally comparable data on the lived experience of persons with spinal cord injury (SCI) in all 6 WHO regions. The InSCI survey provides a crucial first step to generate evidence on functioning, health maintenance, and subjective well-being in persons with SCI globally. A major challenge in setting up the InSCI community survey was to develop a data model and questionnaire that comprehensively captures what matters to people and, at the same time, is feasible and parsimonious in terms of participant's burden. This paper outlines the components of the InSCI data model and presents the question selection to operationalize the data model along the 4 guiding principles of efficiency, feasibility, comparability, and truth and discrimination. The data model consists of 6 components operationalized with 125 questions including functioning (n = 28 body functions and structures; n = 42 activities and participation), contextual factors (n = 26 environmental; n = 19 personal factors), lesion characteristics (n = 2), and appraisal of health and well-being (n = 8). The InSCI questionnaire presents an efficient and feasible solution with satisfying comparability to other populations; however, its validity and reliability still needs to be confirmed.